THE CORRELATION BETWEEN STUDENTS’ LEARNING STRATEGY AND STUDENTS’ ENGLISH ACHIEVEMENT TO THE EIGHTH GRADE STUDENTS OF SMPN H. WUKIRSARI - Agus Triyogo; Hardiyanto Syaprizal (Universitas Lambung Mangkurat, 2018)
This study tried to investigate the correlation between students’ learning strategy and students’ English achievement to the eighth-grade students of SMPN H. Wukirsari. There were two problems which discussed in this study. First was there any correlation between students’ learning strategy and students’ English achievement to the eighth-grade students of SMPN H. Wukirsari? Second, what was the percentage of Students’ Learning Strategy? The objectives of this study were to find out the percentages of students’ learning strategy and to find out the correlation between students’ learning strategy and students’ English achievement to the eighth-grade students of SMPN H. Wukirsai. The method used in this study was correlation research. The population of this study was all of the eighth-grade students of SMPN H. Wukirsari in the academic year 2015/2016. The total number of population was 182 students which were distributed into six classes. There were 28 students treated as the sample of the study. The sample was taken through random sampling. In collecting the data of students’ learning strategy, the writer used questionnaire by strategy inventory for language learning and in collecting the data of students’ English achievement, the writer used students’ report score. Then, the technique for analyzing the data, the writer used Spearman Rank Correlation to find out the correlation between students’ learning strategy and students’ English achievement. Based on the findings, the result of the calculation correlation between students’ learning strategy and students’ English achievement was 0.542, whereas the coefficient of correlation was 0.318 (obtained > table ). So the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, it means that there was a correlation between students’ learning strategy and students’ English achievement to the eighth-grade students of SMPN H. Wuirsari in the academic year of 2015/2016. Finally, the aim of this article was to clarify on students’ learning strategy and students’ English achievement.